MENUMBUHKAN MINAT BELAJAR BAHASA INGGRIS DAN MENINGKATKAN NILAI KEAGAMAAN MELALUI STORYTELLING DI NAGARI TLUK KUALO INDRAPURA - Musdizal, Musdizal; Kamil, Dairabi; Fajri, Kelvin Rahmat (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of community service entitled Improvement in English through Storytelling at TPQ Al Kautsar Tluk Kualo is to provide storytelling training to increase understanding of English at TPQ Al Kautsar Tluk Kualo students. The problem students face in understanding English is that students have never received storytelling material religion taught at TPQ Al Kautsar Tluk Kualo. The step taken in this community service is to conduct a series of storytelling training activities for students to provide training to TPQ Al Kautsar students. The results of community service conclude that there is an increase in understanding of English in TPQ Al Kautsar students. Indications of improvement in the understanding of English in TPQ Al Kautsar Tluk Kualo, 10 students, can be seen based on observations made by the community service team.